Synergy and collaboration of pentahelix elements in strengthening indonesian cultural identity to strengthen nationalism in the era of the industrial revolution 4.0 - Jessica Wijaya; Muhammad Jailani; Jacob Shimrumun Ioraa (Universitas Tanjungpura, 2023)
Indonesia is a multicultural country that has a very complete and diverse cultural portrait. However, as we enter the era of the Industrial Revolution 4.0, which is characterized by rapid technological development, efforts are needed to strengthen Indonesia's cultural identity through the pentahelix concept to ensure that nationalism does not fade. The purpose of this research is to examine the role of pentahelix elements in strengthening cultural identity and what strategies are offered by pentahelix elements to strengthen nationalism in the era of the Industrial Revolution 4.0. This research was conducted using descriptive qualitative methodology to reveal roles and strategies through interviews, observation, documentation, and a literature review to collect data. The informants in this study amounted to eight people, consisting of two people from the government, two people from the education world, one person from the business world, two people from the community, and one person from the media. The results showed that the synergy and collaboration of the pentahelix elements (government, academic, business, community, and media) following with their respective fields contributed to maintaining the existence and preservation of Indonesia's national culture. This is expected to become a pillar and strength of the nation in strengthening Indonesia's cultural identity to strengthen nationalism in the era of the Industrial Revolution 4.0